Analysis of Penggaron Terminal User Activities Using Person-Centered Maps, Place-Centered Maps, and Physical Trace Methods - Anggraini, Dini Silvia; Ikhsani, Muhammad Azmy; Masyitoh, Husnul; Pratama, Hilba Yoga (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
Penggaron Terminal in Semarang City, as one of the main terminals, faces problems related to the use of space that is not optimal. Many users prefer to do activities around the red light at the terminal entrance rather than inside the terminal itself, which causes vehicle congestion and illegal bus parking. This study aims to optimize the use of the terminal and overcome the problem of illegal parking by using the Person Centered Maps, Place Centered Maps, and Physical Trace methods. These methods are used to map user movement patterns, identify space usage, and analyze physical traces left at the terminal. The results of the study indicate that users gather more often outside the terminal, and there is irregularity in the management of space and parking that affects the smoothness of traffic. Based on this analysis, it is recommended to rearrange the parking area, improve facilities inside the terminal, and install clear signs to optimize the function of the terminal. The implementation of this solution is expected to improve the safety, comfort, and efficiency of terminal use, as well as support the smooth flow of traffic around the Terminal area.